The Role of Grand/Mothers' Ways of Knowing in West Coast Latina Students' Collegiate Experiences - Monica Quezada Barrera; Hannah L. Reyes; Antonio Duran; Jeanett Castellanos; Jonathan J. O'Brien (MDPI AG, 2024)
Through a Chicana/Latina Feminist lens centering ways of knowing, we highlight how Latina abuelas and mothers often serve as unofficial teachers in their grand/daughter's educational trajectories. Specifically, through dichos and consejos, these Latina maternal figures impart the knowledge necessary to navigate incongruent educational spaces and persist.